2019
DOI: 10.4142/jvs.2019.20.e35
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced protective immune response to PCV2 adenovirus vaccine by fusion expression of Cap protein with InvC in pigs

Abstract: The major immunogenic protein capsid (Cap) of porcine circovirus type 2 (PCV2) is critical to induce neutralizing antibodies and protective immune response against PCV2 infection. This study was conducted to investigate the immune response of recombinant adenovirus expressing PCV2b Cap and C-terminal domain of Yersinia pseudotuberculosis invasin (Cap-InvC) fusion protein in pigs. The recombinant adenovirus rAd-Cap-InvC, rAd-Cap and rAd were generated and used to immunize pigs. The phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…PCV2 capsid (Cap) protein is a viral nucleocapsid protein encoded by open reading frame 2 (ORF2) and contains specific antigenic determinants [8]. The Cap protein is the major immunogenic structural protein of PCV2 and is responsible for neutralizing antibodies and inducing humoral and cellular immunity [9][10][11]. Therefore, the Cap protein is an important target in the design of a novel PCV2 vaccine using genetic engineering technology.…”
Section: Introductionmentioning
confidence: 99%
“…PCV2 capsid (Cap) protein is a viral nucleocapsid protein encoded by open reading frame 2 (ORF2) and contains specific antigenic determinants [8]. The Cap protein is the major immunogenic structural protein of PCV2 and is responsible for neutralizing antibodies and inducing humoral and cellular immunity [9][10][11]. Therefore, the Cap protein is an important target in the design of a novel PCV2 vaccine using genetic engineering technology.…”
Section: Introductionmentioning
confidence: 99%
“…e spleen is the Evidence-Based Complementary and Alternative Medicine largest immune organ in the body and contains a large number of lymphocytes. Lymphocyte proliferation is an important index of the cellular immune response [54]. Based on a previous finding that HSPT could regulate the numbers of T cells to improve the body's immunity [25], we addressed whether HSPT mediates splenic lymphocyte proliferation induced by CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant adenovirus vaccine demonstrates a potent immune response and superior protection and is expected to become a candidate vaccine for PCVAD [75]. In addition, studies have shown that the Yersinia pseudotuberculosis invasin (Inv) protein can enhance the immune response and can be used to construct a recombinant adenovirus containing the PCV2b Cap gene and InvC gene, which has a good immune response [76].…”
Section: Viral Vectored Vaccinesmentioning
confidence: 99%